영남좌도 통신사 교방춤에 나타난 문화예술적 특징 - 양지선(Ji-Seon Yang); 강인숙(In-sook Kang) (한국콘텐츠학회 논문지, 19(4), 2019)
This study is aimed at researching Gyobang Dance performed by gisaeng of Gyobang in the banquet of Tonshinsa in Yeongnam Jwa-do Province. For this study, Hae-haeng-chong-che, a collection of 28 travel essays written by Joseon Tonshinsa after visiting Japan, and a collection of literary works were analyzed. Joseon Tonshinsa used Yeongnam Jwa-do Province as a route to Japan in obedience to a royal command, and Yeongnam U-do Province as a way back to Hanyang after completing their missions. The country gave a huge banquet to relieve Tonshinsa's anxiety about the voyage and to pray for a safe trip. The banquets were concentrated in Yeongnam Jwa-do Province, the way down to Busan departing from Hanyang. Looking into Tonshinsa's records, it can be seen that Tonshinsa banquets took place in Andong, Yeongcheon, Gyeongju, Milyang, and Busan. Gyobang Dance performed at Tonshinsa banquets includes Geommu, Hwangchangmu, Cheoyongmu, Cheondo, Mudong, Ipchum, and Jungchum. Through Tonshinsa envoy, 'Jeseon Tonshinsa-gil' was formed in Yeongnam Jwa-do Province, and through Tonshinsa banquets, the artistry of Gyobang Dance was compiled. Nevertheless, present Yeongnam Jwa-do Province has remarkably less Gyobang Dance passed down in comparison to Yeongnam U-do Province. For this reason, there is a need to look into Gyobang Dance of Yeongnam Jwa-do Province. The purpose of this study is to closely examine the cultural and artistic characteristics of Gyobang Dance performed at Tonshinsa banquets in Yeongnam Jwa-do Province formed through Joseon Tonshinsa-gil. 본 논문은 영남좌도 통신사 연향에서 교방(敎坊)의 기녀들이 춘 교방춤을 연구한 것이다. 이 연구를 위해 조선통신사들이 일본을 다녀온 후 기록한 28권의 기행문을 엮은 "해행총재(海行摠載)"와 문집류를 분석하였다. 통신사가 왕명을 받들고 일본으로 가는 길은 영남의 좌도(左道)를 이용했고, 임무를 마치고 한양으로 돌아가는 길은 영남의 우도(右道)를 이용했다. 나라에서는 통신사들의 항해에 대한 불안감을 덜어주고 무사안일을 기원하기 위해 성대한 연향을 베풀었다. 연향은 통신사들이 한양을 출발하여 부산으로 가는 하행길인 영남좌도에 집중되었다. 통신사들의 기록을 살펴본 결과 통신사 연향(宴享)은 영남좌도의 안동 영천 경주 밀양 부산 등에서 나타났다. 통신사 연향에 나타난 교방춤은 검무 황창무 처용 천도 무동 입춤 중춤이다. 통신사행을 통해 영남좌도는 '조선통신사 길'이 형성되었고 통신사 연향을 통해 교방춤의 예술성이 집대성되었다. 그러나 현재 영남좌도는 영남우도에 비해 전승되고 있는 교방춤이 현저히 적은 편이다. 이러한 이유로 영남좌도의 교방춤을 살펴볼 필요가 있다. 연구자는 조선통신사 길을 통해 형성된 영남좌도의 통신사 연향에 나타난 교방춤의 문화예술적 특징을 살펴보는 것이 연구의 목적이다.